Bibliometric Analysis of ICT Research in South Africa - Malele, Vusumuzi; Sekwatlakwatla, Sello Prince (Jurnal Pustaka Ilmiah, 2024)
Most of the new fixed and wireless communication networks are being provided by local businesses and foreign subsidiaries, indicating the rising popularity of South Africa's ICT sector in the continent's rapidly expanding market. This study analyzes information and communication technology (ICT) research in South Africa and suggests potential development areas in the country's ICT literature. The study focused on publications that published most ICT research articles for 2009–2024. The study conducted bibliometric analysis based on the number of South African publications and citations in ICT research as indexed in the Scopus and Web-of-Science databases. University of South Africa (UNISA) produced 77% of publications between 2009 and 2024. The University of Pretoria (UP) curriculum aligns with worldwide standards. It gives students a thorough grasp of computer science, emphasizing modern software development techniques used in the IT sector. In the same period, the University Of Pretoria (UP) came in second with 49% followed by the University of Cape Town (UCT) at 41%, the University of Johannesburg (UJ) at 29%, The Council for Scientific and Industrial Research (CSIR) at 28%, followed by University of KwaZulu-Natal at 20%, the North-West University (NWU) at 18% followed by University of Western Cape at 15%, University of Fort Hare at 14%, and Tshwane University of Technology, at 13%. Most research areas were education, educational research, information science, library science, environmental sciences, astronomy, astrophysics, multidisciplinary sciences, computer science, and information systems. During this period, South Africa experienced minimal to no publication in ICT research by universities of technology and colleges. The main contribution of this study is to investigate the prevalence of ICT research in South Africa and provide recommendations on how to improve ICT research.